A 'giant' purgatoriid (Plesiadapiformes) from the Paleocene of Montana, USA: mosaic evolution in the earliest primates. (1st December 2014) - Fox, Richard C.; Scott, Craig S.; Buckley, Gregory A.; Goswami, Anjali
Abstract Ursolestes perpetior gen. et sp. nov. is a large purgatoriid plesiadapiform primate from the middle/late Puercan (earliest Paleocene) Simpson Quarry, Montana, USA. It differs from Purgatorius Van Valen and Sloan, 1965, the only other known purgatoriid and the oldest discovered primate, in its substantially larger body size as inferred from the dimensions of the known parts of its dentition, while resembling Purgatorius in possessing a large lower canine, unreduced p1, and in the upper molars, a protocone twist and weakly developed postprotocone fold; moreover, the m3 of U. perpetior possesses an expanded, plesiadapiform‐like posterior lobe of the talonid that supports the hypoconulid. The large lower canine and the greater development of trenchant molar crests suggest that U. perpetior was more insectivorous, differing appreciably from the omnivorous niche long hypothesized for Purgatorius and purportedly marking the insectivore–primate transition. Hence, U. perpetior adds significant new knowledge regarding the breadth of the adaptive zone occupied by purgatoriids in their position at the very beginnings of primate evolution.